ANALYSIS OF RICE SUPPLY AND PRICES IN INDONESIA, 2000-2023 - Pakpahan, Agrevina; Alamsyah, Zulkifli; Rahayu, Vika Indah (Universitas Jambi, 2026)
Rice is a strategic commodity in Indonesia, serving as the primary staple food. This research aims to describe the trends in rice supply, demand, and prices (2000–2023), analyze the factors influencing price volatility, and predict these conditions for the 2026–2030 period. Using national time-series data, a simultaneous equation system model was estimated using the Two-Stage Least Square (2SLS) technique. The results indicate that while supply is highly volatile, demand has grown more rapidly, triggering an average price increase of Rp496/kg per year. Demand is the most dominant factor positively influencing price. The ex-ante simulation (2026–2030) reveals that a 5% increase in per capita income is predicted to raise price by 13.92%, while a 25% increase in government rice stocks is projected to raise price by 10.53% due to the absorption of supply for reserves. Distinguishing it from previous regional studies, this research provides a comprehensive national-scale analysis over 24 years by integrating imports and government stocks as endogenous variables. Rice price stabilization cannot be achieved abruptly; rather, it requires preventive measures by maintaining the balance between supply and demand, controlling population growth, and implementing strict distribution oversight to prevent speculative practices in the marketing chain. Keywords: Demand, Import, Price, Rice, Supply